ANTIFUNGAL ACTIVITY OF ANABAENA VARIABILIS AGAINST PLANT PATHOGENS - ARCHANA TIWARI; AKSHITA SHARMA (International Journal of Pharma and Bio Sciences, 2013)
Cyanobacterial secondary metabolites have a diverse antagonistic activity that lead to disintegration of microbial growth. The study was conducted to evaluate the antifungal property possessed by cyanobacteria- Anabaena variabilis in retarding the growth of plant pathogenic fungal species. It was observed that the extracts prepared from Anabaena variabilis were capable of diminishing the growth and further development of plant pathogenic fungal strains- Aspergillus niger and Rhizopus stolonifer. Based on zone of inhibition formation, it was concluded that the extracts of Anabaena had significant antifungal efficacy. In addition, methanol and ethanol extracts of Anabaena exhibited maximum antifungal activity against plant pathogenic fungal strains. The antimicrobial attribute of cyanobacteria is due to the presence of cyclic peptide, alkaloids and lipopolysaccharides. Cyanobacteria can be excellent biocontrol sources for plant pathogenic fungi as they can be easily cultured, less expensive compared to synthetic fungicides and ecofriendly, rather they can also promote plant growth and increase the fertility of the soil. The investigation, certainly points out the necessity of exploring new cyanobacterial strains as potentially outstanding sources of antifungal drugs.